The effect of nutritional intervention on the lipid profile and dietary intake of adolescents with juvenile systemic lupus erythematosus: a randomized, controlled trial. (April 2018) - da Silva, S G L; Terreri, M T; Abad, T T O; Machado, D; Fonseca, F L A; Hix, S; Suano-Souza, F I; Sarni, R O S; Len, C A
Objective: This study sought to evaluate the effects of a nutritional intervention on the lipid metabolism biomarkers associated with cardiovascular risk, and their variation over time, in juvenile systemic lupus erythematosus (JSLE) patients. This study also investigated the relationships between these biomarkers and dietary intake, nutritional status, disease variables, and medication used. Methods: A total of 31 10- to 19-year-old female adolescents with JSLE for at least six months were analyzed. The participants were randomly allocated to two groups: nutritional intervention or control. The intervention group received verbal and printed nutritional instructions once per month over nine months. Before and after the intervention, the participants underwent assessments of anthropometry; dietary intake; physical activity; socioeconomic status; total cholesterol and fractions; triglycerides; apolipoprotein A (Apo A-I); apolipoprotein B (Apo B); paraoxonase (PON) activity (a) and amount (q); myeloperoxidase (MPO); and small, dense LDL-c (sdLDL) particles. Results: After nine months, we found significant reductions in the calorie, carbohydrate, total fat, saturated fat, and trans fat intakes in the intervention compared with the control group over time. The PONa/HDL-c ratio increased by 3.18 U/ml/mg/dl in the intervention group and by 0.63 U/ml/mg/dl in the control group ( p  = 0.037). Unlike the intervention group, the sdLDL levels of the control group worsened over time ( p  = 0.018). Conclusion: The present study detected a reduction in calorie and fat intake, which indicates an improvement of HDL-c function and possible protection against cardiovascular risk for the intervention group.